Evaluation of efficacy and safety of glucokinase activators—a systematic review and meta-analysis - Yang, Wenjia; Wu, Han; Cai, Xiaoling; Lin, Chu; Jiao, Ruoyang; Ji, Linong (Frontiers in Endocrinology, 2023)
Aims: Glucokinase activators (GKAs) promote the activity of glucokinase (GK) and is under development for the treatment of diabetes. The efficacy and safety of GKAs require evaluation. Methods: This meta-analysis included randomized controlled trials (RCTs) with a duration of at least 12 weeks conducted in patients with diabetes. The primary objective of this meta-analysis was the difference of hemoglobin A1c (HbA1c) change from baseline to study end between GKA groups and placebo groups. Risk of hypoglycemia and laboratory indicators were also evaluated. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated for the continuous outcomes, odd ratios (ORs) and 95% CI were calculated for the risk of hypoglycemia. Results: Data from 13 RCTs with 2,748 participants treated with GKAs and 2,681 control participants were analyzed. In type 2 diabetes, the level of HbA1c decreased greater in patients with GKA treatment compared with placebo (WMD=-0.339%, 95% CI -0.524 to -0.154%, P＜0.001). The OR comparing GKA versus placebo was 1.448 for risk of hypoglycemia (95% CI 0.808 to 2.596, P=0.214). The WMD comparing GKA versus placebo was 0.322mmol/L for triglyceride (TG) levels (95% CI 0.136 to 0.508mmol/L, P=0.001). When stratified by drug type, selectivity, and study duration, significant difference was found between groups. In type 1 diabetes, the result of HbA1c change and lipid indicators showed no significant difference between TPP399 group and placebo group. Conclusions: In patients with type 2 diabetes, GKA treatment was associated with a better glycemic control, but significant elevation in TG concentration in general. The efficacy and safety varied with drug type and selectivity.